Tortoise Love: DH Lawrence on Reptile Orgasm - Jonathan Pollock (Caliban: French Journal of English Studies)
In his exploration of sexual desire, the English novelist and poet D.H. Lawrence does not confine himself to the ardours of human beings, Ursula Brangwen, Constance Chatterley or other Women in Love. A sequence of poems devoted to tortoises interrogates the manifestations of love and desire among cold-blooded creatures—“Tortoise Shell,” “Lui et Elle,” “Tortoise Gallantry,” “Tortoise Shout”—as well as the consequences of such gallantry: “Baby Tortoise,” “Tortoise Family Connections.” In my examination of these poems, I shall attempt to determine whether Lawrence is guilty of blatant anthropocentricity or whether something of the alien nature of another species finds its way into his writing, thereby attesting to his near-shaman-like capacity for cross-species communication and empathy.